IoT based Fire Alerting Smart System - Ibtehal Mahfoodh Mohammed Al Hasani; Syed Imran Ali Kazmi; Reehan Ali Shah; RAZA HASAN; Saqib Hussain (Sir Syed University Research Journal of Engineering and Technology, 2022)
By combining IoT devices, such as fire alarm systems (smoke and high-temperature sensors), sensors, and other supplementary equipment, the research paper offers the "IOT based Fire Alerting Smart System" in smart buildings. The research article proposes the "IOT based Fire Alerting Smart System" in smart buildings by merging IOT devices such as fire alarm systems (smoke burn with high-temperature sensors), sensors, and other auxiliary equipment. That notification includes the time and location of fire occurs.  Comparing two existing smart IoT-based fire warning systems from around the world.  The Internet of Things is designed to provide organisations and individuals more visibility, and it now has the ability to govern 99 percent of available surroundings and objects that aren't connected to the Internet. Thus, IOT will be able to accomplish more meaningful work at a higher level by creating opportunities for individuals and businesses so that they can engage more with the outside world more than ever. Old fire alarm systems include many different types of devices that play a particular role in the workings of the system, detecting a person and detecting and wearing out a person through visual and auditory devices in the event of fire, smoke, monoxide carbon or others emergency. These types of alarms can be actuated by manual focus or manual fire alarms, such as suction stations, and can be activated automatically on smoke and heat detectors. The alarm can come with an electric chime. A horn or wall speaker can be a bright tone for a speaker that sounds an alarm; for example, you can add an audio evacuation message to warn you about using the elevator and other warning messages to users.